2015
DOI: 10.1227/neu.0000000000000892
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Resolution Magnetic Resonance Elastography in Meningiomas to Determine Intratumoral Consistency

Abstract: Introduction Magnetic Resonance Elastography (MRE) analyzes shear waves’ movement thorough tissue to determine stiffness. In a prior study, measurements using first-generation brain MRE techniques correlated with intraoperative observations regarding overall meningioma stiffness. We evaluated the diagnostic accuracy of a higher-resolution MRE technique to preoperatively detect intratumoral variations as compared to surgeon assessment. Methods Fifteen meningiomas in fourteen patients underwent MRE. Tumors wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 13 publications
1
61
0
Order By: Relevance
“…MRE is a dynamic technique that measures shear wave movement through tissue to determine consistency [20]. All three studies that reviewed MRE supported its use to predict consistency [6, 20, 23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRE is a dynamic technique that measures shear wave movement through tissue to determine consistency [20]. All three studies that reviewed MRE supported its use to predict consistency [6, 20, 23].…”
Section: Discussionmentioning
confidence: 99%
“…endoscopic) intracranial tumor resection necessitates a reliable, non-invasive technique to predict consistency. Softer tumors would purportedly be easier to remove endoscopically, while firmer tumors may require a traditional open approach, especially around the skull base [20, 25, 32]. A validated preoperative neuroimaging strategy using would obviously be of great value to both surgeon and patient in informing surgical planning, operative strategy, and patient counseling.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, conventional measurements based on T1WI and T2WI may best predict only very soft or hard tumors. A subsequent prospective study by the same group used higher-resolution MRE in an attempt to better capture the intratumoral heterogeneity of consistency 34 . They found that higher-resolution (3 mm isotropic resolution as opposed to 4 mm performed in Murphy et al 32 ), had high specificity and positive predictive value to detect heterogeneity and hard consistency.…”
Section: Neuroimaging Studies Of Meningioma Consistencymentioning
confidence: 99%
“…Currently, MRE is a clinical tool to stage liver fibrosis and has been validated against liver biopsy 20 . MRE has also been used to detect liver tumors 21 , brain tumors 22 , and Alzhemiers 23 . MRE has recently been successfully applied invivo to measure the stiffness of the human aorta 24-27 and also in animals, which are validated against ex-vivo mechanical testing 28 , histopathology 29 and PWV 24, 27 .…”
Section: Introductionmentioning
confidence: 99%